1998
DOI: 10.1080/14017439850140238
|View full text |Cite
|
Sign up to set email alerts
|

Activated and Total Coagulation Factor VII, and Fibrinogen in Coronary Artery Disease

Abstract: Fibrinogen (FBG) and total coagulation factor VII (FVIIc) concentrations are higher in those patients with coronary artery disease who are at increased future risk of acute ischemic events. The relationship between activated factor VII (FVIIa) and cardiovascular events, however, has not been intensively studied. Data were collected from 401 consecutive patients who underwent coronary angiography because of suspected coronary artery disease. Conventional risk factors FVIIc, FVIIa and FBG were assessed in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…FVIIa may play an important role in a hypercoagulable state 23 . Increased FVII has been shown to be a risk factor for coronary heart disease 24 . In our study, we found a decrease in factor VIII and X activity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…FVIIa may play an important role in a hypercoagulable state 23 . Increased FVII has been shown to be a risk factor for coronary heart disease 24 . In our study, we found a decrease in factor VIII and X activity.…”
Section: Discussionsupporting
confidence: 62%
“…23 Increased FVII has been shown to be a risk factor for coronary heart disease. 24 In our study, we found a decrease in factor VIII and X activity. VWF and FVII activity did not change in hypothyroid patients.…”
Section: Discussionsupporting
confidence: 58%
“…Population studies have reported that fVII levels are unrelated to the degree of carotid artery thickness or other manifestations of vascular disease (Folsom et al ., 1993; Koster et al ., 1994; Moor et al ., 1995; Sosef et al ., 1994; Vaziri et al ., 1992). Results have been mixed with regard to a potential correlation between fVIIa levels and the risk of thrombotic disease (Kalaria et al ., 2000) (Danielsen et al ., 1998; Cooper et al ., 2000). …”
Section: Tf:viia In Diseasementioning
confidence: 99%
“…F1+2 formed by the transformation of prothrombin to thrombin and serving as a marker of ongoing coagulation [29], FVIIa which together with tissue factor initiates the coagulation cascade through the extrinsic pathway and, if elevated, may reflect a hypercoagulable state [9], and FVIIc which has been associated with an increased risk of coronary events [30, 23] – we found no significant relation to the vitamin D levels nor did we find any other studies where this was evaluated.…”
Section: Discussionmentioning
confidence: 99%